Geoheritage and Geotourism Resources - Santangelo, Nicoletta; Valente, Ettore (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue outlines the role of geoheritage and geotourism as potential touristic resources of a region. The term "geoheritage" refers to a particular type of natural resources represented by sites of special geological significance, rarity or beauty that are representative of a region and of its geological history, events, and processes. These sites are also known as "geosites" and, as well as archaeological, architectonic, and historical sites, can be considered as part of the cultural estate of a country. "Geotourism" is an emerging type of sustainable tourism, which concentrates on geosites, focusing on visitor knowledge, environmental education, and amusement. Geotourism may be very useful for geological sciences divulgation and may provide additional opportunities for the development of rural areas, generally not included among the main touristic attractions. The collected papers focused on these main topics with different methods and approaches and can be grouped as follows: i) papers dealing with geosite promotion and valorization in protected areas; ii) papers dealing with geosite promotion and valorization in non-protected areas; iii) papers dealing with geosite promotion by exhibition, remote sensing analysis, and apps; iv) papers investigating geotourism and geoheritage from tourists' perspectives.